2005
DOI: 10.1111/j.1471-0528.2005.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of a new handheld vacuum extraction device

Abstract: Objective To evaluate the effectiveness of a new handheld vacuum delivery device.Design Randomised controlled trial.Setting Southmead Hospital, Bristol, UK.Population One hundred and ninety-four women requiring delivery with vacuum extraction.Methods Women were recruited into the study while still in early labour. If during delivery, vacuum extraction was indicated they were then randomly allocated to either a new handheld vacuum device, the Kiwi Omnicup, or to a 'standard' vacuum cup selected by the obstetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
3
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 12 publications
8
64
3
8
Order By: Relevance
“…7 The disposable rigid vacuum devices have been reported to have failure rates of up to 34%. 8,9 This supports the argument for better training to conduct operative vaginal deliveries. 10,11 Currently, the trainee operator's level of expertise depends on the number of procedures carried out and on the knowledge, skill and enthusiasm of the teacher.…”
Section: Introductionsupporting
confidence: 54%
“…7 The disposable rigid vacuum devices have been reported to have failure rates of up to 34%. 8,9 This supports the argument for better training to conduct operative vaginal deliveries. 10,11 Currently, the trainee operator's level of expertise depends on the number of procedures carried out and on the knowledge, skill and enthusiasm of the teacher.…”
Section: Introductionsupporting
confidence: 54%
“…Judging by recent reports from other teaching institutions in the UK, failure rates for vacuum extraction of 20% or higher are not uncommon. 13,14 Clearly, the DDI will be influenced by the number of failed procedures that are followed by additional methods to complete the delivery.…”
mentioning
confidence: 99%
“…As previous clinical studies have shown [3] [7]- [9], this is expected to lead to an improvement in clinical outcomes by decreasing vacuum delivery failure rates, especially in mal positions. In each of the three workshops the participants independently developed the same technique for cup insertion.…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide variation between reported failure rates depending on the fetal head position, the choice of cup and the skill of the accoucheur [8] [9]. Failure rates differ with different types of cup used [2] but even using the same cup (Kiwi Omnicup) failure rates vary from 2% to 34% [3] [7] [10]. It is widely accepted that the key to minimising failure rates and fetal trauma is accurate cup placement over the flexion point [4] [10] [11].…”
Section: Introductionmentioning
confidence: 99%